2012
DOI: 10.1002/path.4072
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of human glioblastoma vessels indicates a key role of VEGF‐A and TGFβ2 in vascular abnormalization

Abstract: Glioblastoma are aggressive astrocytic brain tumours characterized by microvascular proliferation and an abnormal vasculature, giving rise to brain oedema and increased patient morbidity. Here, we have characterized the transcriptome of tumour-associated blood vessels and describe a gene signature clearly associated with pleomorphic, pathologically altered vessels in human glioblastoma (grade IV glioma). We identified 95 genes differentially expressed in glioblastoma vessels, while no significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 67 publications
(82 reference statements)
8
128
0
Order By: Relevance
“…However, additional studies are required to determine the functional significance of DNA methylation, if any, at these genes. Our finding of differentially methylated/accessible genes previously shown to harbor mutations in GBM-COL19A1 (Sumiyoshi et al 1997), CD93 (Dieterich et al 2012), AGAP2 (Knobbe et al 2005), and ACSL5 (Mashima et al 2009)-supports the validity of this approach in identifying GBM-relevant epigenetic perturbations. Interestingly, most of the genes that were identified as differentially methylated between GBM and NSC were classified as variably methylated in NSC (Table 4, lower).…”
Section: Discussionsupporting
confidence: 78%
“…However, additional studies are required to determine the functional significance of DNA methylation, if any, at these genes. Our finding of differentially methylated/accessible genes previously shown to harbor mutations in GBM-COL19A1 (Sumiyoshi et al 1997), CD93 (Dieterich et al 2012), AGAP2 (Knobbe et al 2005), and ACSL5 (Mashima et al 2009)-supports the validity of this approach in identifying GBM-relevant epigenetic perturbations. Interestingly, most of the genes that were identified as differentially methylated between GBM and NSC were classified as variably methylated in NSC (Table 4, lower).…”
Section: Discussionsupporting
confidence: 78%
“…In line with our initial finding on elevated CD93 expression in glioblastoma vasculature, a subsequent study identified CD93 as one of the top genes of a core human primary tumor angiogenesis signature, highly expressed in head and neck squamous cell carcinomas, breast cancers, and clear cell renal cell carcinomas (7,15). These studies are the first ones to report CD93 as a tumor vascular marker.…”
Section: Discussionsupporting
confidence: 62%
“…Previously, we reported that these pathologically altered vessels in grade IV glioma express high levels of CD93, a transmembrane protein from the C-type superfamily of lectins with a calcium-dependent carbohydrate-binding domain (7). CD93 was initially suggested to play a role in angiogenesis due to its high expression in areas of blood vessel remodeling in the developing vasculature of mouse embryos (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations